Desert tourism between the need for development and response to demand The case of the city of Béni Abbés - Algeria - Benaissa, Fateh Toufik; Hadj, Hafsi lahcen; Dehimi, Salim; Allal, Ahmed (Technium Social Sciences Journal, 2022)
Desert tourism is a tool for economic and social development, which makes it unique, especially if it is based on effective foundations and ingredients that contribute to the national and local economy. However, promoting tourism in desert countries and regions requires policies and strategies that work hard to build infrastructure (airports, roads, railways, hotels, and provide services of all kinds), provide security, and hire experts in tourism consulting. The tourist region of the southwest of Algeria in general witnessed a significant increase in the number of international visitors and tourists during the colonial era and after independence. The city of Béni-Abbés in particular, as well as the entire province of Bechar, is famous for being great tourist destinations. However, due to the particular neglect of desert tourism in this region, the number of arrivals has decreased significantly, especially in recent periods, which has affected the general situation of tourism and attractive beavers. In order to revitalize desert tourism and address the problems that have been highlighted, immediate action is needed.